Double-Cavity Fabry–Perot Interferometer Sensor Based on Polymer-Filled Hollow Core Fiber for Simultaneous Measurement of Temperature and Gas Pressure - Yixin Zhu; Yufeng Zhang; Qianhao Tang; Shengjie Li; Huaijin Zheng; Dezhi Liang; Haibing Xiao; Chenlin Du; Yongqin Yu; Shuangchen Ruan (Sensors)
A double-cavity Fabry-Perot (F-P) interferometer sensor based on a polymer-filled hollow core fiber (HCF) has been proposed and experimentally verified. The double cavity of the sensor is formed by filling the hollow core fiber with two kinds of polymer materials and curing these materials, with the other end of the hollow core fiber connected to a single-mode fiber (SMF). The three reflective surfaces of the sensor reflect three beams of light, which interfere to form a spectrum with an envelope. By using Fast Fourier Transform (FFT) and a Fourier filter, the spectrum of each cavity can be separated and, based on this, the demodulation matrix of the sensor can be constructed. By controlling the length of the polymer cavity, a single sensor cavity can achieve high temperature and gas pressure sensitivity, with values of 2.05 nm/°C and 17.63 nm/MPa, respectively. More importantly, the sensor can be used under an environment of 40–110 °C and 0–3.0 MPa, with simple fabrication, good robustness, and better stability and repeatability compared to similar sensors. Based on its high sensitivity and large measurement range, this sensor has broad application prospects in industrial manufacturing and harsh environmental monitoring fields.